Swedish School Leaders Go Online - Carlén, Urban; Jobring, Ove (Proceedings of the International Conference on Networked Learning, 2006)
Swedish school leaders are gathered in a pilot project called School Leaders Online . To build a nation-wide Online Professional Community, Swedish National Agency for School Improvement implemented threaded forums as a tool for school leaders to share experiences about their common topics and work practice. Qualitative methods are used in order to show that participation in an informal learning setting is dependent on how school leaders negotiate meaning of their conditions at work, common topics for constructing knowledge and the capabilities to appropriate threaded forums. One conclusion will explain the importance of using several online tools in learning experiences.